Lower Salinity Leads to Improved Physiological Performance in the Coccolithophorid Emiliania huxleyi, Which Partly Ameliorates the Effects of Ocean Acidification - Xu, Jiekai; Sun, Jiazhen; Beardall, John; Gao, Kunshan (Frontiers in Marine Science, 2020)
While seawater acidification induced by elevated CO2 is known to impact coccolithophores, the effects in combination with decreased salinity caused by sea ice melting and/or hydrological events have not been documented. Here we show the combined effects of seawater acidification and reduced salinity on growth, photosynthesis and calcification of Emiliania huxleyi grown at 2 CO2 concentrations (low CO2 LC：400 μatm; high CO2 HC：1000 μatm) and 3 levels of salinity (25, 30 and 35‰). A decrease of salinity from 35 to 25‰ increased growth rate, cell size and photosynthetic performance under both LC and HC. Calcification rates were higher in the LC compared to the HC-grown cells only at 25‰ salinity, with insignificant changes under 30 and 35‰ levels. Since salinity and OA treatment did not bring about interactive effects on calcification, changes in calcification are attributed to the elevated dissolved inorganic carbon concentration, with higher ratios of calcification to photosynthesis in the cells grown under 35‰ compared with those grown at 25‰. In contrast, photosynthetic carbon fixation increased almost linearly with decreasing salinity, regardless of the pCO2 treatments. When subjected to short-term exposure to high light, the low-salinity-grown cells showed the highest photochemical effective quantum yield with the highest repair rate, though the HC treatment enhanced the PSII damage rate. Our results suggest that Emiliania huxleyi can tolerate low salinity plus acidification conditions by up-regulating its photosynthetic performance, but shows a relatively insensitive calcification response, which may help it better adapt to future ocean global environmental changes, especially in the coastal areas of high latitudes.